Investigation of the Interaction of Herbal Ingredients Contained in Triphala Recipe Using Simplex Lattice Design: Chemical Analysis Point of View - Chaowalit Monton; Thaniya Wunnakup; Jirapornchai Suksaeree; Laksana Charoenchai; Natawat Chankana (International Journal of Food Science)
The aim of this work was to investigate the interaction of herbal ingredients contained in Triphala recipe (Terminalia chebula, Terminalia bellirica, and Phyllanthus emblica in equal proportion) using simplex lattice design. This work focused on chemical analysis of four phenolic compounds including gallic acid, corilagin, chebulagic acid, and chebulinic acid by validated high-performance liquid chromatography. The effect of the extraction technique (decoction vs. infusion) and gamma irradiation was also examined. The combination index was used as a tool for determination of interaction of the ingredients contained in the herbal recipe. Results showed that the extraction technique and gamma irradiation slightly altered the content of some phenolic compounds as well as the combination index. The positive interaction seems to be found at the equal proportion of the three plants. This work scientifically supported the suitable formula of the Triphala recipe in the traditional use.